Strengthening Character Education Through School Culture Based Habituation in Developing Interpersonal Relationships at Elementary School of Alam Al Fatih Palu - Alfian Akbar; Andi Anirah; Dzakiah, Dzakiah; Hartati, Hartati (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
This research aims to analyze the forms and implementation of Strengthening Character Education through school culture based habituation in developing students interpersonal relationships at SD Alam Al Fatih Palu. Using a qualitative approach, data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data display, and conclusion drawing. The results indicate that school culture based habituation integrating values of discipline, empathy, cooperation, and effective communication into daily activities is proven to significantly strengthen students interpersonal relationships. Furthermore, synergy between the school, parents, and the community serves as a supporting factor in creating harmonious social relationships. This study concludes that the comprehensive integration of character in both academic and non academic aspects is essential to create an educational environment conducive to students social development.